“Welfare Is Everybody’s Responsibility”—or No One’s? On the (Im)possibilities of Mental Health First Aid in the Neoliberal University - Kent, Aimee; Coen, Stephanie E.; Clare, Nick (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
The neoliberal university, by commodifying and individualising learning, teaching and research, has been linked to growing mental health issues and presents many challenges for delivering adequate mental health services. We use concepts of critical geographies, including mutual aid, as a framework to explore the potential of Mental Health First Aid (MHFA) as a ‘care-full’ intervention within the neoliberal university environment. Through a case study of MHFA-trained staff at a research-intensive university in the United Kingdom, we analyse the tension MHFA holds of being instrumentalised by the neoliberal university while also holding potential as a care-full tool for mutual aid. Our analysis demonstrates that schemes to achieve support and uptake. At the same time, it became evident that uncertainty with role boundaries and the delegation of responsibility for welfare in the campus environment created confusion about the role of MHFA and revealed a tension between commitments to cultivating an ethic of care whilst resisting a neoliberal individualisation of responsibility. We conclude that, despite this potential, MHFA, in our empirical case study, is limited by its role boundaries and risks becoming a neoliberal problem itself. Yet, MHFA could open up advantageous responses to neoliberal challenges if framed and implemented effectively, with a clear focus on building care-full communities and valuing mutual aid.